The interaction between acute emotional states and executive functions in youth elite soccer players - Knöbel, Simon; Weinberg, Henrietta; Heilmann, Florian; Lautenbach, Franziska (Frontiers in Psychology, 2024)
Executive functions (EFs) are relevant for game performance in soccer and have been investigated in previous research. However, emotions are a well-known performance factor in sport competitions, which may affect performance by means of EFs. The diagnostic of EFs has mainly been performed disregarding the potential impact of emotional states. Thus, we aimed to initially analyze interaction between emotional states and EFs in two studies with male youth elite soccer players. In the first study, 105 players (Mage = 14.97) completed computerized tasks assessing inhibition, cognitive flexibility and working memory. In the second study, 92 players (Mage = 15.17) performed adapted and validated tests of inhibition (n = 45) or cognitive flexibility (n = 47) in a soccer-specific setting (SoccerBot360). Emotional and affective states were assessed using the German Sport Emotion Questionnaire and self-assessment manikins. For the computerized tasks, results showed a significant negative correlation between switch costs accuracy and tension, r = -.28, indicating lower error rates with higher levels of tension. In contrast, in the SoccerBot360 we found significant positive correlations for response time and tension (no-switch: r = .38; switch: r = .39) representing prolonged response times related to tension. Further, for soccer-specific inhibition, positive emotions were significantly positively correlated with response time (congruent: r = .32; incongruent: r = .32). Subsequent regression analyses also demonstrate that valence and arousal effectively explain variance in cognitive performance parameters under neutral conditions. Accordingly, the ambiguity of the results suggests high variability in EF performance, affective and and emotional statess as well as a potentially moderating influence of other variables such as context and task difficulty. Thus, future cognitive diagnostic research should integrate assessments of emotional and affective states as these may contribute to situational fluctuations in EF performance.